Project Siemen Craft / Mohd Faidzul Amar... [et al.] - Amar, Mohd Faidzul; Zainol Abidin,, Muhd Imanuddin; Mohd Mihron, Mohd Azam; Mohd Yusof, Mohamad Sufian; Hasim, Azwan (2000)
Dynamic Kraft Sdn Bhd was establish and industry of manufacturing or producing cement pillars. This company handles all of the duties and responsibilities given to each members under the name of “Dynamic Kraft Sdn Bhd”. The company is registered as a partnership company under the Partnership Act 1961. The business involving pillars making under the manufacturing industry. They provide various types of pillars with high rank of qualities with reliable and affordable price. Nowadays, the industry of pillar making has the potential to grow in the future and procedures large scale demand by different races throughout the country, therefore they believe and confident that this industry has the potential in gaining profit and it will also increase demand and attracting various races in and out of the country. This company operates in Sg, Petani Kedah.